1998
DOI: 10.1063/1.368856
|View full text |Cite
|
Sign up to set email alerts
|

Recrystallization kinetics of electroplated Cu in damascene trenches at room temperature

Abstract: Cu metallization for sub-0.25 μm interconnects marks not only a change in metallurgy from Al and a change in architecture from subtractive to damascene but also a major shift in deposition technology from sputtering to electroplating. A remarkable feature of electroplated Cu films is the recrystallization or grain growth process that takes place at room temperature over a period of hours to weeks after plating. While this phenomenon has been described for blanket films, the influence of substrate topography on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
139
1
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 216 publications
(149 citation statements)
references
References 9 publications
8
139
1
1
Order By: Relevance
“…Several mechanisms that could drive such a transformation have been proposed, including defect, grain-boundary, and surface energies, but also chemical gradients in the material that can cause diffusion-induced grain-boundary migration [84]. During the last decade, microstructural evolution or self-annealing has been observed in electroplated copper films that are stored at room temperature [44,[85][86][87][88][89]. Although this behaviour of electroplated copper is intriguing, the kinetics are hard to study, since the as-deposited grain structure and impurity content of the film strongly depend on the electroplating bath chemistry.…”
Section: Self-annealing In Electroplated and Sputtered Copper Filmsmentioning
confidence: 99%
“…Several mechanisms that could drive such a transformation have been proposed, including defect, grain-boundary, and surface energies, but also chemical gradients in the material that can cause diffusion-induced grain-boundary migration [84]. During the last decade, microstructural evolution or self-annealing has been observed in electroplated copper films that are stored at room temperature [44,[85][86][87][88][89]. Although this behaviour of electroplated copper is intriguing, the kinetics are hard to study, since the as-deposited grain structure and impurity content of the film strongly depend on the electroplating bath chemistry.…”
Section: Self-annealing In Electroplated and Sputtered Copper Filmsmentioning
confidence: 99%
“…1,2 Since the era of copper interconnects this socalled self-annealing effect came into focus. [3][4][5] Selfannealing has been recognized as an unwanted side effect in the successful manufacturing of copper thin films for applications in microelectronics and postdeposition annealing at elevated temperatures for stabilizing the microstructure has been introduced as an integrated part of the manufacturing process. Even so self-annealing can be prevented by intentional annealing at elevated temperatures, the phenomenon remains of scientific and technological interest, since understanding the kinetics and mechanisms of self-annealing is the essence of tailoring the microstructure.…”
Section: Introductionmentioning
confidence: 99%
“…10 Several publications, however, have suggested that in narrow lines, high dislocation density, seed layer texture, and minimization of the Cu-Ta interfacial energy cause coarsening of grains in the trenches prior to the overburden. 8,11,12 In this work, TEM analysis of samples during and after the transformation is presented supporting the trench-initiated recrystallization hypothesis, and goes further to show that the microstructure inside the trenches is stable well before the transformation in the overburden is complete.…”
mentioning
confidence: 69%